G206 Does Increased Duration of Consultant Presence Affect Length of Hospital Stay for Unplanned Admissions in Acute Paediatrics?: An Observational Before-And-After Analysis Using Administrative Healthcare Data. (24th May 2017) - Cromb, D; Carter, C; Lemer, C; Cheung, CR
Abstract : Objectives: This study aims to review whether implementation of increased duration of consultant presence is associated with reduction in length of hospital stay (LoS) in children with an unplanned admission to hospital. Method: An observational before-and-after study of all unplanned general paediatric admissions to a UK hospital between 1 September 2012 and 31 August 2015, comparing LoS and readmission rates before and after implementation of a policy mandating consultant review within 12 hours of unplanned hospital admission. Results: 5367 inpatient admissions were analysed: 3386 prior to implementation of the policy and 1981 afterwards. There was no significant difference in median LoS between the two groups or in readmission rates at 24 hours, 48 hours or 7 days. However, among children who stayed in hospital for under 24 hours, and those who were discharged with a diagnosis of acute gastroenteritis, consultant review within 12 hours of admission was associated with a shorter LoS— respectively, 16 hours 23 min versus 15 hours 45 min (p=0.01) and 28 hours 46 min versus 19 hours 41 m (p<0.01). Conclusions: Increased duration of consultant presence was not associated with significant impact on LoS, other than in admissions of brief duration and in gastroenteritis, where diagnosis is based on clinical judgement in the absence of objective diagnostic thresholds. Future studies should focus on whether these results are generalisable across other settings, and other measures of cost-effectiveness of early consultant review, given the major implications on resource and workforce planning of such policies.